Efficient Generation of Unmarked Deletions in Legionella pneumophila - Bryan, Andrew (American Society for Microbiology (ASM), 2011)
Unmarked gene deletions facilitate studies of Legionella pneumophila multicomponent processes, such as motility and exonuclease activity. For this purpose, FRT-flanked alleles constructed in Escherichia coli using λ-Red recombinase were transferred to L. pneumophila by natural transformation. Resistance cassettes were then efficiently excised using the Flp site-specific recombinase encoded on a plasmid that is readily lost.